P85 A retrospective analysis of five years of referrals for haemoptysis under the two-week-wait pathway to a university teaching hospital. (12th November 2019) - Hameed, F; Kang, J; Gleeson, F; Wrightson, J; Moore, A; Sykes, A
Abstract : Background: Patients with haemoptysis are often referred via the two-week-wait (2ww) suspected lung cancer pathway. CXR has poor sensitivity and most patients undergo a Computed Tomography (CT) scan. Previous studies have suggested that CT may miss small lesions in up to 5% of the cancer cases leading to fibreoptic bronchoscopy (FOB) also frequently being performed. 1 We performed a retrospective analysis of five years of patients presenting with haemoptysis of unknown cause to Oxford University Hospitals NHS Foundation Trust (OUHFT), to determine the utility of CT and FOB. Study hypothesis: In patients with haemoptysis and normal CT chest, FOB does not identify further cancers. Aims: To evaluate the utilisation of CT and FOB in patients with haemoptysis referred via two-week-wait pathway. Methods: A retrospective non-randomised analysis was conducted of a total of 402 patients who were referred to OUHFT between 2013 and 2017 with haemoptysis of unknown cause. The records were reviewed and findings of CT, FOB and final diagnosis assessed. Results: A total of 402 patient records were reviewed. Mean age 62.58 years (SD 14.20), males 65.4%, females 34.6%, mean smoking pack-years 22.29 (SD 25.52), 26.4% current smokers, 47.5% ex-smokers and 26.1% non-smokers. Of 402 cases, 34.6% (n=139) had normal CT and 65.4% (n=263) had abnormal CT. Of 263, the common CT results were infective features in 73, features of malignancy in 41 and bronchiectasis in 20. Of 402 cases, FOB was done in 140. Of these, 90 cases had normal FOB and a cancer was diagnosed in 11. Of these 11, all had definite or possible features of malignancy already identified on CT. There were no additional cancers found by FOB in patients having had a normal CT. When it comes to final diagnosis, the common findings were idiopathic haemoptysis in 33.3% (n=134), infection in 32.8% (n=132) and primary or metastatic lung cancer in 9.5% (n=38). Conclusion: In conclusion, in our study, FOB did not reveal a malignancy or a significant non-malignant abnormality, if the CT was normal. We recommend that assessment of haemoptysis in outpatient setting should mainly rely on clinical and radiological assessment and bronchoscopy should only be considered on individual basis rather than being considered routine. References: Hirshberg B, et al . Hemoptysis: etiology, evaluation, and outcome in a tertiary referral hospital. Chest 1997;112:440–4.